2007
DOI: 10.1021/ic701650y
|View full text |Cite
|
Sign up to set email alerts
|

The Presumption of Innocence? A DFT-Directed Verdict on Oxidized Amavadin and Vanadium Catecholate Complexes

Abstract: 51V NMR chemical shifts have been computed at the GIAO-B3LYP level for non-oxo vanadium(V) complexes related to oxidized amavadin, [Delta-VV{(S,S)-hidpa}2]- (H3hidpa = 2,2'-hydroxyiminodipropionic acid). According to model calculations, the unusual deshielding of the 51V resonance is due to a combination of conventional substituent effects (e.g., oxo vs dihydroxo or alkoxy vs carboxylato ligands), rather than to a non-innocent nature of the hidpa ligand. For selected diastereomeric vanadium hidpa complexes, Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 62 publications
(102 reference statements)
7
42
0
Order By: Relevance
“…Similar behavior was reported in a previous study of vanadium complexes with oxyamine ligands where substantial errors were observed for δ zz , the chemical shift component perpendicular to the oxyamine plane. 24, 32 The fact that even at this level of theory difficulties are encountered in describing the interaction between the three-membered oxyamine-vanadium is consistent with the well-known problems with calculations of these strained compounds. The lower calculated anisotropies suggest that the molecule is less symmetric than the models used and indicate that the calculations underestimate the bonding between the vanadium and the oxyamine unit when using the X-ray structures.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Similar behavior was reported in a previous study of vanadium complexes with oxyamine ligands where substantial errors were observed for δ zz , the chemical shift component perpendicular to the oxyamine plane. 24, 32 The fact that even at this level of theory difficulties are encountered in describing the interaction between the three-membered oxyamine-vanadium is consistent with the well-known problems with calculations of these strained compounds. The lower calculated anisotropies suggest that the molecule is less symmetric than the models used and indicate that the calculations underestimate the bonding between the vanadium and the oxyamine unit when using the X-ray structures.…”
Section: Resultssupporting
confidence: 61%
“…17, 18, 23, 24, 32, 3842 Table 1 contains the results of calculations performed on the HIDA and HIDPA complexes using three functionals, b3lyp, PBE1PBE, and PBEPBE, and three basis sets, 6–311++G(d,p), 6–311++G, and tzvp as available in the Gaussian03 program. 43 The results obtained for the quadrupolar coupling constant and the asymmetry parameters of the EFG tensor for the HIDPA complex are in good agreement with experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in this calculation, the principal components of the computed CSA tensor are also in reasonable agreement with the experiment ( δ σ agrees to within 90 ppm, and η σ –to within 0.04) and the computed values are similar to the previously reported calculations conducted at a comparable level of theory. 66 …”
Section: Resultsmentioning
confidence: 99%
“…66 DFT calculations generally predict the NMR parameters accurately. However, when a ligand is non-innocent with large 51 V isotropic chemical shifts, the experimentally observed de-shielding is less well described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation